Intraprocedural reduction of the veno-arterial norepinephrine gradient correlates with blood pressure response after renal denervation - Tiroch, Klaus; Sause, Armin; Szymanski, Jacek; Nover, Ina; Leischik, Roman; Mann, Johannes; Vorpahl, Marc; Seyfarth, Melchior (EuroIntervention, 2015)
No intraprocedural assessment is currently available to evaluate the extent of nerve ablation by renal denervation (RDN). We prospectively evaluated the association of intraprocedural reduction of renal veno-arterial norepinephrine gradient with blood pressure (BP) response after RDN.In 46 consecutive RDN patients, the periprocedural norepinephrine veno-arterial difference was defined as veno-arterial norepinephrine gradient. We observed a reduction of the office systolic BP from 176±19 mmHg to 165±24 mmHg (p=0.02) at three months and 163±22 mmHg (p=0.02) at six months. The mean and maximum systolic ABP decreased by 5 mmHg (p=0.03) and 9 mmHg (p=0.02), respectively. There was a decrease of the norepinephrine RV-RA difference from pre- to post-procedural levels (median 186 pg/ml [54;466] vs. 81 pg/ml [0;182], p=0.02). OBP responders (office systolic BP reduction >=10 mmHg) showed a greater reduction of the norepinephrine gradient compared to non-responders (-290±450 pg/ml vs. -4±106 pg/ml, p=0.01). Patients with a reduction of norepinephrine gradient in both kidneys showed the most pronounced decrease of the systolic OBP (-24±14 mmHg) compared to patients with a reduction of norepinephrine gradient in only one kidney (-7±15 mmHg) or patients without a norepinephrine reduction (-3±19 mmHg, p=0.03 vs. bilateral reduction).Measuring renal norepinephrine gradient during RDN may be a method to gauge the extent of renal nerve ablation.
EVALuna2:3874